RELEVANSI KONSEP PENDIDIKAN ISLAM KH. AHMAD DAHLAN DI ABAD 21 - Putri Yuliasari (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2014)
The education according to Islam is the part of work for human to de responsibly. In order that, Islam surely gives the basic concepts about an education and it becomes the responsibility for human to explicit by aplicating those basic concepts in the practice of education. One of the intelectual moslems which is trying to reconstruct the paradigm building that can be a basic of National Education system is K.H Ahmad Dahlan. Referrring to that background, it can be attractted one problem related to the thoughts of K.H Ahmad Dahlan about the concept of Islamic education and the relevantion of K.H Ahmad Dahlan’s Thoughts to the concept of Islamic education in age 21. The thought of K.H Ahmad Dahlan about the concept of Islamic Education may be seen from his efforts in integrating dichotomyof knowledge, keeping the balance, patterning intelectual, attitude and religious. The aim of Islamic education referring to him is to bear individu in whole. In the framework to integrate two sysstem of education, K.H Ahmad Dahlan more adobts education system from western school which is on one step forward. The thought of K.H Ahmad Dahlan has a relevancy when it is faced to the context of Islamic education in age 21. The thought of K.H Ahmad Dahlan about concept of Islamic education is the one of alternative ways that can be realized to find the way of education problem in age 21